Definition of the words “Hydrographer” and “Hydrography” - Dodd Nares, John (The International Hydrographic Review, 2025)
This manuscript is a reprint of the original paper previously published in 1934 in the Hydrographic Review, a predecessor journal of The International Hydrographic Review (IHR, https://ihr.iho.int/): Nares, J. D. (1934). Definition of the words “Hydrographer” and “Hydrography”. Hydrographic Review, 11 (1), 8-11. https://journals.lib.unb.ca/index.php/ihr/article/view/28159